Integration of mobile and web application : an implementation of diabetic management system - A. Jabar, Marzanah; Azmi, Mohammad Fazli; Sidi, Fatimah (Asian Research Publication Network, 2013)
Rapid development and high mobile devices penetration around the globe has impacted wireless and flexibility usage that promotes usability of technology at anytime and anywhere. Wireless technology has turned out to be the major medium in communication. One of the best-known examples of wireless technology is the mobile phone that can help to create solutions faster and easier than earlier days.However, designing and implementing these types of information systems can be highly challenging and difficult as user interaction with such technologies will be continuous and pervasive. Therefore, we propose a solution on how to deliver and share information in an ubiquitous environment.A prototype of diabetes monitoring system that support both mobile and web platform were implemented and evaluated.An evaluation based on expert judgment technique was used to validate the prototype. This study has shown that integration with mobile and web to access information on the internet can be a paradigm to promote ubiquitous information access and sharing.